1998
DOI: 10.1139/x97-208
|View full text |Cite
|
Sign up to set email alerts
|

Coarse woody debris in sub-boreal spruce forests of west-central British Columbia

Abstract: An evaluation of how coarse woody debris (CWD) changes in quantity and quality during stand development was conducted using a 426-year chronosequence of 71 stands in sub-boreal forests in British Columbia. Additional characteristics of CWD were determined in 14 of the stands. Most stands are fire initiated and input from the predisturbance stand is critical in controlling the amounts and characteristics of CWD within young stands. Log volume declines from over 100 m3/ha in young stands (0-50 years) to just ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 18 publications
6
30
0
Order By: Relevance
“…In earlier studies, snag abundance has been observed to follow a well-defined U-shaped pattern over stand age. This pattern is characterized by high volume of snags in stands recently disturbed by fire, few snags in actively growing stands, and an increasing snag abundance in ageing stands as canopy trees become progressively senescent (e.g., Harmon et al 1986, Spies and Franklin 1988, Tyrrell and Crow 1994, Clark et al 1998). In the course of this long-term stand development, other forest attributes may change, including species composition and tree size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier studies, snag abundance has been observed to follow a well-defined U-shaped pattern over stand age. This pattern is characterized by high volume of snags in stands recently disturbed by fire, few snags in actively growing stands, and an increasing snag abundance in ageing stands as canopy trees become progressively senescent (e.g., Harmon et al 1986, Spies and Franklin 1988, Tyrrell and Crow 1994, Clark et al 1998). In the course of this long-term stand development, other forest attributes may change, including species composition and tree size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The species of snag was determined when possible and the degree of decay was estimated using a six-class system from Lee et al (1995). Stand age was determined by taking increment cores from all 20 live trees in each sampled stand and assigning the stand age to equal the oldest tree that was no more than 10 years older than another tree in the stand (Clark et al 1998). The diameter of all downed woody material (DWM) greater than 10 cm was measured along five equally spaced and parallel 20-m long transects, two of which formed the boundaries of the larger 20-m 2 sampling quadrat.…”
Section: Methodsmentioning
confidence: 99%
“…Advanced stages of forest succession lead to canopy break-up, release of understorey plants, accumulation of snags and downed logs, and the emergence of secondary canopy species (Peterson et al 1995, Schneider 2000. Typically, structural diversity is greatest in older forest stands (Clark et al 1998, Burton et al 1999, Lee et al 2000. This diversity tends to result in diverse plant and wildlife communities that differ significantly from those found in younger stands (Farr 1993, Roy et al 1995, Kirk et al 1996, Gandhi et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…Stem exclusion with stand maturation, one of the main factors regenerating snags, is also closely related to stand age (Oliver andLarsen 1996, Lee et al 1997). Relationships between snag abundance and stand age in managed forests vary from insignificant and inconsistent (Clark et al 1998, Grove 2001, DeWalt et al 2003 to positive (Mannan et al 1980, Sturtevant et al 1997, Lee 1998, Hale et al 1999). However, because these studies were not conducted in plantations, similar studies in plantations are required to develop ecologically sustainable plantation management guidelines.…”
Section: Introductionmentioning
confidence: 99%